Rethinking Competition Law within the European Economic Constitution. (16th January 2019) - Gerbrandy, Anna
Abstract: In light of re‐conceptualizing a European social market economy, this contribution considers competition law's position in the European economic constitution. The economic constitution captures the economic foundation of European integration as based on the market mechanism. The contribution asks whether the change towards a 'more economic approach' to competition law implies an alienation of competition law from societal challenges. The contribution considers whether this interpretation, with competition law being such an integral part of the European economic constitution, should change in light of the constitutional goal of a European social market economy. To do so, the article sketches the fundamental place of competition law in the European economic constitution and shows how its interpretation has become more economics‐based. It highlights some of the problematic aspects of this change and analyzes these findings from the perspective of an economic constitution serving a social market economy.